Good literature and bad literature: debate on Islam and poetry - Hasan, Md. Mahmudul (Bangladesh Institute of Islamic Thought (BIIT), 2014)
As regards Islam and poetry (for that matter, literature as a whole), there exists some misunderstanding which is most commonly made by two mutually opposing groups: commentators with negative notion about Islam who state that it is a restrictive religion with no room for creativity; and devout Muslims with somewhat puritan tendency who believe that all sorts of entertainment production and consumption including poetry are prohibited in Islam. Interestingly, both the groups use similar kinds of Qur’anic and Hadith texts to pass their verdicts on the subject. This article revisits some of those revealed texts and provides the author’s thoughts on the debate on Islam and poetry. It also identifies types of literature which Islam approves and some other literary productions which Islam discourages.